IMPLEMENTATION OF EFFECTIVE ORAL CORRECTIVE FEEDBACK IN ENGLISH LANGUAGE CLASSES - Muhammadali Adhamjonov (Journals Park Publishing, 2022)
Modern renewal of the content and structure of education requires radical revision of the relationship between the teacher and the student, in particular profiling of a teacher from the head of educational activities which should control the process of mastering knowledge by students, in an equal participant in this process. In order to feel confident in this role, the teacher must be well acquainted with the methods and technology of such training, test and experience it for you. Creation of favorable a pleasant learning environment is impossible without the implementation of feedback, which allows the teacher to regularly monitor and adjust the process obtaining knowledge by students. The following article is devoted to delivering corrective feedback effectively in foreign language classes.
Keywords: feedback; method; visual feedback